2019
DOI: 10.1186/s40854-019-0139-z
|View full text |Cite|
|
Sign up to set email alerts
|

The interaction effect of foreign capital inflows and financial development on economic welfare in sub-Saharan Africa

Abstract: This study examines the interaction effects of foreign capital inflows and financial development on economic welfare in sub-Saharan Africa (SSA). Estimates based on the system-GMM estimator using panel data on 23 SSA countries for 2000 to 2013 establish several results. First, the interaction between foreign capital inflows and financial development positively affects economic welfare in SSA. However, this effect was negative after one year. Second, the partial indirect effects of foreign capital inflows on ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…With appropriate Chinese investor decisions and a favorable business environment in the host countries, the efficiency of Chinese OFDI could be significantly improved [2]. However, as most existing studies have analyzed Chinese OFDI location choice determinants based on aggregate OFDI data [3][4][5][6][7][8][9], the specific determinants in each industry have not been distinguished. Further, because of potential extreme values, aggregate OFDI data can suffer from skewed data structures, which may adversely affect model fit and estimations [10].…”
Section: Introductionmentioning
confidence: 99%
“…With appropriate Chinese investor decisions and a favorable business environment in the host countries, the efficiency of Chinese OFDI could be significantly improved [2]. However, as most existing studies have analyzed Chinese OFDI location choice determinants based on aggregate OFDI data [3][4][5][6][7][8][9], the specific determinants in each industry have not been distinguished. Further, because of potential extreme values, aggregate OFDI data can suffer from skewed data structures, which may adversely affect model fit and estimations [10].…”
Section: Introductionmentioning
confidence: 99%
“…Though this theoretical model is designed for the analysis of health production at the micro-level, it can be used at the macro level without losing its theoretical foundation. 22,30 At the macro-level analysis, the health production inputs are grouped into economic, social, environmental, and health service utilization variables, which are mostly represented at their per capita levels as given in Equation [2].…”
Section: The Frameworkmentioning
confidence: 99%
“…where H is a vector of health outcomes per capita; Y is a vector of economic variables per capita; S is vector of social variables per capita; E is vector of environmental variables; and D is a vector of health service utilization variables. The scalar form of Equation [2] can be given as in Equation [3]. [3] can be transformed in an explicit form by formulating probability density for the y, s, e and d variables as given in Equation [4].…”
Section: The Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Schotten and Morais (2019) indicated that investment and capital gains increase due to transparency in decision making and lead to a level of protection for organisational goals. Acheampong (2019) pointed out that harmony in financial development occurs through compatibility between foreign capital and developing individual's demand.…”
Section: The Effects Of Saving and Capital Expansion On Financial Developmentmentioning
confidence: 99%